Analisis Tindak Pidana Dengan Sengaja Menyebarkan Informasi Kebencian Dan Sara Melalui Media Sosial (Studi Kasus Putusan Nomor 177/Pid.Sus/2021/PN Jkt.Brt) - Agus Dwi Setiyono (Peneliti.net, 2023)
The application of material criminal law against perpetrators of criminal acts of spreading hatred and sara information through social media is carried out through an integrated criminal justice system involving the police, prosecutors, courts and correctional institutions. Hate speech through social media that causes hostility among groups in society. The act of spreading hate speech through social media is prohibited and punishable in Article 28 paragraph (2) jo Article 45 paragraph (2) of Law Number 11 of 2008 concerning ITE which carries a maximum imprisonment of 6 (six) years. The Panel of Judges in handing down a verdict against the perpetrator of the crime of spreading hatred and sara information through social media in Decision Number 177/Pid.Sus/2021/PN Jkt.Brt. on the spread of hate speech through social media Based on the testimony of witnesses and the testimony of the defendant, the existence of evidence and the facts revealed in court, on the elements of Article 28 paragraph (2) jo Article 45A paragraph (2) of Law No.19 of 2016 concerning Amendments to Law No.11 of 2008 concerning ITE, the Panel of Judges has correctly argued the elements charged from the Public Prosecutor.